2019
DOI: 10.1038/s41467-019-11356-w
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved NMR monitoring of tRNA maturation

Abstract: Although the biological importance of post-transcriptional RNA modifications in gene expression is widely appreciated, methods to directly detect their introduction during RNA biosynthesis are rare and do not easily provide information on the temporal nature of events. Here, we introduce the application of NMR spectroscopy to observe the maturation of tRNAs in cell extracts. By following the maturation of yeast tRNA Phe with time-resolved NMR measurements, we show that modifications are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 69 publications
2
83
0
1
Order By: Relevance
“…LC-MS/MS analyses can reproducibly quantify individual RNA modifications in purified tRNAs as shown by analysing six LC-MS/MS measurements on commercially available tRNA-Phe from Saccharomyces cerevisiae (supplementary Figure 3A and B confirming the analysis of S.c. tRNA-Phe published in [53]). 5ʹ tsRNA-Gly GCC/CCC and 5ʹ tsRNA-Glu CUC/UUC along with their remaining parental full-length tRNAs were purified from biological triplicate experiments after either iAs exposure or ecANG expression followed by LC-MS/MS analyses (Fig.…”
Section: Determining the Modification Status Of Purified Tsrnasmentioning
confidence: 99%
“…LC-MS/MS analyses can reproducibly quantify individual RNA modifications in purified tRNAs as shown by analysing six LC-MS/MS measurements on commercially available tRNA-Phe from Saccharomyces cerevisiae (supplementary Figure 3A and B confirming the analysis of S.c. tRNA-Phe published in [53]). 5ʹ tsRNA-Gly GCC/CCC and 5ʹ tsRNA-Glu CUC/UUC along with their remaining parental full-length tRNAs were purified from biological triplicate experiments after either iAs exposure or ecANG expression followed by LC-MS/MS analyses (Fig.…”
Section: Determining the Modification Status Of Purified Tsrnasmentioning
confidence: 99%
“…U55 to Ψ55 as observed in yeast 22 . In fact, we observe 1.5 fold more Ψ in the early lifetime of tRNA Phe GAA as is expected from mature tRNA Phe GAA (Figure 1).…”
Section: Temporal Placement Of Modified Nucleosides In Rnamentioning
confidence: 67%
“…By NMR spectroscopy in combination with stable isotope labeling, Barraud et al recently observed an inhibition of m 22 G formation by m 2 G 22 . In our hands, m 22 G is placed into tRNA Phe as fast as is m 2 G, but as both modifications are incorporated slowly it is possible that m 22 G is placed in a non-m 2 G modified sub-population. This question might be approached by combining NAIL with oligonucleotide MS.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations